Reaksi Saham BUMN terhadap Kepemimpinan Erick Thohir - Fitriani Fitriani; Ulin Alfina (Mabsya: Jurnal Manajemen Bisnis Syariah, 2020)
State owned Enterprise have arole as national economic actors. However, the policy issued by the minister of SOES will affect the structural and internal af the companies. The purpose of this study is to determine the reaction of SOES company share to the policy. The research used is quantitative descriptive reseach event study method. The population in this study were 20 SOES companies listed on the IDX with a sample of 5 SOES companies listed on the IDX the experienced structural changes due to Erick Thohir’s policy. The technical analysis is by companing the average price 5 days before at the event (H-), the stock price at the time of the event (H), and the average price 5 days after the event (H+), the results of this study are an insignificant decline in four of the five companies share occurred only a few days abd rose again indicating its influencer is not significant.Keywords: Reaction, stoks, and policy.